The Sociology as a Social Science in Brazil (Estudios Sociales, 2021)
In recent decades there has been an intense movement from the international sociology to revisit the different national traditions of formation of this science, recognizing the different forms of institutionalization and development that it has assumed. In order to contribute to this debate, I analyze in this article the formation of sociology in Brazil, highlighting the idiosyncratic aspects that it has in comparison with other national traditions, emphasizing its institutionalization through secondary school, as well as the existence of a formation of sociologists through interdisciplinary undergraduate social science courses. I also highlight the growing process of sociology's autonomization in relation to the other social sciences, which in my interpretation, connects with the development of the postgraduate programs in sociology.
Keywords: Brazilian sociology; Latin American sociology; history of sociology